1889
DOI: 10.2475/ajs.s3-37.220.310
|View full text |Cite
|
Sign up to set email alerts
|

Palaeohatteria Credner, and the Proganosauria

Abstract: ONE of the most important discoveries in Paleontology has just been made by Professor H. Oredner of Leipzig, well known by his publications on the Stegocephalia of the Permian of Saxony.* This discovery consists of a series of nearly complete skeletons of a reptile from the lower Permian (Rothliegendes). This reptile, with the exception of Stereosternum Oope, from the Oarboniferous (~) of Brazil, is the oldest yet known. Professor Oredner calls it Palmolwtteria from the close resemblance to EIatteria from New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1962
1962
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Prior to the development of phylogenetic systematics, mesosaurs were assigned to numerous different tetrapod groups. Gervais (1865) considered mesosaurs to be closely related to Sphenodon, whereas Cope (1886) assigned them to "?Batrachia, " Baur (1889) hypothesized that they may be ancestral to amniotes, and von Huene (1941) suggested that they were closely related to basal pelycosaurs. With the advent of phylogenetic systematics, numerous studies incorporated mesosaur taxa into their analyses, the first being the pioneering study by Gauthier et al (1988), which recovered mesosaurs as the sister to all other parareptiles.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the development of phylogenetic systematics, mesosaurs were assigned to numerous different tetrapod groups. Gervais (1865) considered mesosaurs to be closely related to Sphenodon, whereas Cope (1886) assigned them to "?Batrachia, " Baur (1889) hypothesized that they may be ancestral to amniotes, and von Huene (1941) suggested that they were closely related to basal pelycosaurs. With the advent of phylogenetic systematics, numerous studies incorporated mesosaur taxa into their analyses, the first being the pioneering study by Gauthier et al (1988), which recovered mesosaurs as the sister to all other parareptiles.…”
Section: Introductionmentioning
confidence: 99%
“…The term ‘gastralia’ is often used to refer to the elongate ventral ossifications of basal tetrapods because their Λ‐shaped arrangement closely resembles the gastralia or ‘abdominal ribs’ of several amniotes. Indeed, the gastralia of amniotes are probably derived from the ventral scales of basal tetrapods (Baur, 1889; Voeltzkow & Döderlein, 1901; Romer, 1956). In extant crocodilians and Sphenodon , the gastralia develop in the dermis and become secondarily embedded in the rectus abdominis muscle later in ontogeny (Voeltzkow & Döderlein, 1901; Howes & Swinnerton, 1901; Claessens, 2004).…”
Section: Definition Of Anatomical Termsmentioning
confidence: 99%
“…Mesosauridae Baur 1889 Dejinition. The last common ancestor of Mesosaurus, Brazilosaurus and Stereosternum, This taxon is supported by eleven synapomorphies: 24* and all its descendants (Baur, 1889;Carroll, 1988;Lydekker, 1889).…”
mentioning
confidence: 99%